Association between dental neglect and alexithymia among adult dental patients - Nitya Krishna Nanamadri; Dolar Doshi; Suhas Kulkarni; Madupu Padma Reddy; Adepu Srilatha (Wolters Kluwer Medknow Publications, 2021)
Aims: To show the association between dental neglect and alexithymia among adult dental patients. Settings and Design: At times, certain individuals with dental neglect may experience trouble in communicating and/or understanding information, ability to identify, and describe their feelings termed as alexithymia. Hence, recognition of alexithymia in a dental setting is important, because it worsens the dentist-patient relationship, especially among patients who neglect their dental health. Materials and Methods: A cross-sectional survey was conducted among adult patients (≥20 years). Patients received a questionnaire assessing dental neglect [six-item Dental Neglect Scale (DNS)], alexithymia [20-item Toronto Alexithymia Scale (TAS-20)], and demographic profile. Statistical Analysis: Data were analyzed with standard statistical software (Statistical Package for the Social Sciences, version 22). P <0.05 was considered statistically significant. Results: A total sample of 1067 individuals comprising 553 (51.8%) females and 514 (48.2%) males with a mean age 35.33 ± 11.49 years participated in the study. Our findings showed that females had higher mean scores for both DNS and total TAS-20 and its factors. With increase in age and education, the mean scores of the DNS had significantly increased and mean scores of total TAS-20 and its factors had decreased with increase in age and education. Conclusion: The above study findings have supported the hypothesis that there is no association between dental neglect and alexithymia among adult dental patients.